Essential cues of engineered polymeric materials regulating gene transfer pathways. (July 2022) - Ariful Islam, Mohammad; Park, Tae-Eun; Firdous, Jannatul; Li, Hui-Shan; Jimenez, Zuly; Lim, Michael; Choi, Jeong-Won; Yun, Cheol-Heui; Cho, Chong-Su
Abstract: Regulating cellular uptake pathways using engineered materials is becoming a vital strategy for efficient gene transfer because the success of gene delivery most often relies on the uptake mechanism and the intracellular fate of the delivery vectors. The uptake of gene carriers can be greatly affected by the various physical, geometrical, chemical, and biological characteristics of the delivery vectors. In the design of gene delivery materials, it is important to understand not only how gene carriers are taken up and transported into cells, but also how the uptake mechanism can be regulated. In this review, we discuss polymeric materials that regulate cellular uptake pathways for highly effective delivery of gene therapeutics, elucidate various routes of cellular uptake that alter the intracellular fate of polymeric gene carriers and finding efficient strategies for overcoming extracellular and intracellular obstacles. We also discuss the structures of polymeric materials in order to understand how they regulate cellular uptake. Lastly, we discuss various strategic approaches, including essential cues on how to regulate the cellular uptake pathways of polymeric carriers and how to control their endocytic trafficking to improve the efficacy of gene delivery.